Explosion Characterization of Solid Lactic Acid - Martina S. Scotton; Sabrina Copelli; Marco Barozzi; Benedetta A. De Liso; Ernesto Salzano (Chemical Engineering Transactions, 2025)
Lactic acid (LA) is a molecule of significant industrial interest, utilized in various sectors. In the food industry, it is used as a preservative and pH regulator in baked goods, dairy products, and beverages. Additionally, it finds applications in the pharmaceutical industry, where it is used in skincare creams, chemical peels, and as a moisturizing agent. Furthermore, lactic acid is employed in the chemical and textile industries. Conversely, to poly-lactic acid (PLA), its explosiveness and thermodynamic properties are not well-documented in the scientific literature. Indeed, only a few relevant works provide a comprehensive overview of lactic acid properties, applications, and production. However, such reviews neither specifically address the explosiveness of lactic acid nor study its thermodynamic properties, providing valuable data on either its thermal stability or behavior at different temperatures and pressures. This work aims at bridging these lacks by exploring LA (here considered as a racemic mixture of either L or D-lactic acid) thermochemical behavior (through thermogravimetric studies and modelling), explosive potential (calculating either Minimum Ignition Energy, MIE, or Deflagration Index, Kst), and associated safety challenges. Through this work, the authors also wish to provide a foundation for both enhancing industrial safety and unlocking new applications for this versatile compound.